Approach to patients with essential thrombocythaemia and very high platelet counts: what is the evidence for treatment?. (16th December 2016) - Falchi, Lorenzo; Bose, Prithviraj; Newberry, Kate J.; Verstovsek, Srdan
Summary: Treatment of essential thrombocythaemia (ET) is directed at decreasing the risk of complications of the disease, including arterial and venous thrombosis and bleeding episodes. Established risk factors for vascular events in patients with ET include advanced age (>60 years) and prior history of thrombosis or haemorrhage. The role, if any, of other potential risk factors, including cardiovascular risk factors, leucocytosis, high haematocrit, and JAK2 V617F has been analysed in multiple studies. The impact of thrombocytosis on the risk of vascular events has also been investigated. Many clinicians consider an elevated platelet count to be a risk factor for thrombosis or, when extreme, bleeding and utilize this as a criterion to start cytoreductive therapy. However, the relationship between thrombocytosis and vascular events is controversial and solid evidence to support the use of cytoreductive therapy in ET patients who have no other risk factors is lacking. In this review, we discuss current treatment recommendations for patients with ET, the biology underlying vascular events and risk factors thereof. We then review the evidence on the management of patients with ET and extreme thrombocytosis.